2019
DOI: 10.1155/2019/1531567
|View full text |Cite
|
Sign up to set email alerts
|

Do Probiotics Improve the Health Status of Individuals with Diabetes Mellitus? A Review on Outcomes of Clinical Trials

Abstract: Probiotics are now considered as an adjuvant and complementary therapeutic agent for several health complications, especially for metabolic and gastrointestinal disorders because of the influential impact of probiotic consumption on gut microbiota and immunity. Diabetes mellitus (DM) is fourth, in noncommunicable disease category, leading cause of mortality, morbidity, and economic crises in the world. Though several progressions are added in the medical field in recent decades, the treatment and management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…Probiotics including certain genera of Lactobacillus and Bifidobacterium are currently commonly used as human nutrition supplements and meet the goal of a positive effect on human health. In T2D patients, probiotic supplements have been widely studied, and several trials have demonstrated that probiotic intervention could improve fasting blood glucose, HbA1c and insulin sensitivity [ 56 , 57 ]. As a promising probiotic, A. muciniphila is also currently under investigation for use in various diseases, including diabetes [ 41 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics including certain genera of Lactobacillus and Bifidobacterium are currently commonly used as human nutrition supplements and meet the goal of a positive effect on human health. In T2D patients, probiotic supplements have been widely studied, and several trials have demonstrated that probiotic intervention could improve fasting blood glucose, HbA1c and insulin sensitivity [ 56 , 57 ]. As a promising probiotic, A. muciniphila is also currently under investigation for use in various diseases, including diabetes [ 41 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high-caloric diet was proven to have a negative influence on the gut microbiota by lowering the glucose tolerance and by increasing inflammation and intestinal permeability ( Bagarolli et al, 2017 ). Kesika et al (2019) explained that the overall efficacy of RCTs is not clear, due to some limitations, which include sample size, preparation of supplements, monitoring of intervention, sampling strategies, inconsistency in measurements, and questionnaire biasness. Authors stressed that further well-designed studies are required to understand the link between the role of the microbiome, the interaction of probiotics with the host microbiota, and the glycemic control.…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…The F/B ratio was significantly and positively correlated with reduced glucose tolerance ( 29 31 ). Probiotic and synbiotic supplementation had beneficent effects in T2DM by improving glycated hemoglobin (HbA1c), fasting insulin levels, Homeostasis model of assessment-insulin resistance (HOMA-IR), and the quantitative insulin sensitivity check index (QUICKI) ( 32 , 33 ). Probiotics play immunomodulatory roles by downregulating LGI levels, skewing pro-inflammatory macrophages toward a pro-restorative phenotype, increasing the Treg/Th17 ratio, and promoting interferon (IFN) γ-producing Th-1 lymphocytes [reviewed in ( 33 , 34 )].…”
Section: Therapeutic and Preventive Strategiesmentioning
confidence: 99%